The Roles of the State Educational Inspectorate and Monitoring Unit in The Development of Secondary Education in Jigawa State, Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2024)
This study examines the pivotal roles played by the State Educational Inspectorate and Monitoring Unit in the development of secondary education in Jigawa State, Nigeria. Through a comprehensive analysis, the research highlights how these bodies contribute to the enhancement of educational standards, the implementation of policies, and the overall improvement of school management and student performance. Data were collected through surveys and interviews with key stakeholders, including educational inspectors, school administrators, and teachers. The findings reveal significant contributions of the Inspectorate and Monitoring Unit in areas such as curriculum development, teacher training, and the evaluation of teaching methodologies. Additionally, the study identifies challenges faced by these units, including inadequate funding and logistical constraints, and proposes recommendations for strengthening their impact on secondary education. This research underscores the importance of robust educational oversight and monitoring mechanisms in fostering academic excellence and sustainable educational development in Jigawa State.